Activated Carbon/MnO2 Composite as Uranium Adsorbent in Solution - Anjarsari, Nita; Zaharah, Titin Anita; Sayekti, Endah; Yamin, Bohari Mohd. (CHEESA: Chemical Engineering Research Articles, 2024)
This research aimed to make an adsorbent from activated carbon/MnO2 (AC/MnO2) composite and examine its characteristics, adsorption capacity, and mechanism for uranyl ions. Carbon was made from Oil Palm Empty Fruit Bunches (OPEFB) through sodium acetate's carbonization and activation processes. The AC/MnO2 composite was made using the in-situ deposition method, namely by oxidizing Mn2+ compounds to Mn4+ under alkaline conditions at a temperature of ±80°C. An FTIR spectrophotometer was used to characterize the adsorbent, and a UV-Vis spectrophotometer was used to determine the content of uranyl. The results of FTIR analysis showed that MnO2 in Mn-O and Mn-O-Mn absorption was bound to activated carbon. It was also discovered that AC/MnO2 adsorbent reduced uranium content in solution in the form of uranyl ion for adsorbent mass of 2.5 grams and a contact time of 60 minutes, leading to adsorption percentages of 65.5%. The adsorption mechanism followed the Langmuir adsorption isotherm equation by forming a single layer. Meanwhile, the adsorption kinetics followed pseudo-second-order with a value of k = 6.7 g/mg.min.